PUBLIC SECTOR WAGE AND INFLATION IN GHANA - Ofori-Abebrese, Grace; Walanyo Azumah, George Kwesi; Pickson, Robert Becker (Asian Economic and Financial Review, 2018)
Article published in the Asian Economic and Financial Review, 2017, found at DOI: 10.18488/journal.aefr.2017.76.561.572